UJI ANTAGONISME BAKTERI ENDOFIT ASAL TANAMAN PERTANIAN DATARAN RENDAH PADA MEDIUM AGAR - Arika Purnawati; Noni Rahmadhini; Elly Syafriani (UPN VETERAN JAWA TIMUR, 2019)
This research aims to obtain endophytic bacterial candidates from lowland agricultural plants that have potential as biological control agents for Ralstonia solanacearum on tomato plants. Bioassay was carried out using the soaking method of tomato seeds in the suspension of endophytic bacteria (108 cfu / ml) during 60 minutes then R. solanacearum was 24 hours old (108 cfu / ml) mixed with 6 ml of liquid agar 0.6% and poured onto the seed surface. Bioassays were observed at 24, 48, 72 and 96 hours. The study was conducted using Completely Randomized Design (CRD) with 10 endophytic bacterial isolates as single treatment factor and repeated 3 times. The results obtained showed that 10 endophytic bacterial isolates were able to inhibit the growth of R. solanacearum in agar medium, and the highest clear zone size was formed by H, I, J